Non-atopic Neonatal Thymic Innate Lymphoid Cell Subsets (ILC1, ILC2, and ILC3) Identification and the Modulatory Effect of IgG From Dermatophagoides Pteronyssinus (Derp)-Atopic Individuals - de Sousa, Thamires Rodrigues; Sgnotto, Fábio da Ressureição; Fagundes, Beatriz Oliveira; Duarte, Alberto José da Silva; Victor, Jefferson Russo (Frontiers in Allergy, 2021)
Innate lymphoid cells (ILCs) are classified into distinct subsets termed ILC1, ILC2, and ILC3 cells. The existing literature lacks evidence identifying ILCs and their subsets in the human thymus but already demonstrates that they can exert several functions in regulating immune responses. Furthermore, it was already described that IgG's repertoires could modulate lymphocytes' maturation in the human thymus. Here we aimed to identify ILCs subsets in the human thymus and provide insight into the possible modulatory effect of purified IgG on these cells. Thymic tissues were obtained from 12 infants without an allergic background (non-atopic), and a literature-based peripheral ILCs staining protocol was used. Purified IgG was obtained from non-atopic individuals (n-At), atopic individuals reactive to allergens non-related to dust mites (nr-At), and atopic individuals reactive to the mite Dermatophagoides pteronyssinus (Derp-At). As with all tissues in which they have already been detected, thymic ILCs are rare, but we could detect viable ILCs in all tested tissues, which did not occur with the ILC1 subset. ILC2 and ILC3 NKp44+ subsets could be detected in all evaluated thymus, but ILC3 NKp44- subset could not. Next, we observed that Derp-At IgG could induce the expression of ILC2 phenotype, higher levels of IL-13, and lower levels of IL-4 when compared to IgG purified from non-atopic or non-related atopic (atopic to allergens excluding dust mites) individuals. These results contribute to the elucidation of human thymic ILCs and corroborate emerging evidence about IgG's premature effect on allergy development-related human lymphocytes' modulation.